2018
DOI: 10.19044/esj.2018.v14n13p121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Retrenchment on Employees’ Service Delivery: A Study of Ten Districts of Enugu Electricity Distribution Company (EEDC) in Southeast Nigeria

Abstract: This study examines the effect of retrenchment on employees’ service delivery: a study of ten districts of Enugu Electricity Distribution Company (EEDC) in Southeast Nigeria. The study was necessitated by the alarming rate of retrenchment across various industries in Nigeria particularly the energy sector that is a major driver of economic growth and development in the country. The poor service delivery of the sector has been a teething problem to both the citizens and organizations that need their services. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Retrenchment can result in greater burden for survivors, causing stress and decreasing job satisfaction, as well as instilling fear and job insecurity, leading in worse morale and productivity. Survivor guilt may exacerbate mental discomfort and strained professional relationships (Dibua, Idemobi, & Okoli, 2018;Nyaberi & Kiriago, 2013;Brockner et al, 2004;Allen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Retrenchment can result in greater burden for survivors, causing stress and decreasing job satisfaction, as well as instilling fear and job insecurity, leading in worse morale and productivity. Survivor guilt may exacerbate mental discomfort and strained professional relationships (Dibua, Idemobi, & Okoli, 2018;Nyaberi & Kiriago, 2013;Brockner et al, 2004;Allen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The study, however, did not consider the strategies of alleviating the distress experienced by the retrenched individuals which this study seeks to address. Dibua, Idemobi and Okoli (2018) made another study on the effect of retrenchment on employees' service delivery at Enugu Electricity Distribution Company (EEDC) in Southeast Nigeria. The study found that an increased workload and pay cuts made the workers more susceptible to depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%